Block copolymers for designing nanostructured porous coatings - Nisticò, Roberto (Beilstein Journal of Nanotechnology, 2018)
Highly ordered porous coatings find applications in many fields, such as nanotechnology, microfluidics and nanofluidics, membrane separation, and sensing. In recent years, there has been great interest regarding the synthesis of isoporous and well-ordered (in)organic coatings for the production of highly selective functional membranes. Among the different strategies that have been proposed to date for preparing these porous thin coatings, one simple route involves the use of self-assembled amphiphilic block copolymers either as the porogen (acting as sacrificial templating agents for the production of inorganic architectures) or as a source of the porogen (by self-assembly for the production of polymeric substrates). Therefore, an extended discussion around the exploitation of block copolymers is proposed here in this review, using polystyrene-block-polyethylene oxide (PS-b-PEO) as the model substrate, and critical points are highlighted.
Keywords: block copolymers; coatings; materials science; porous materials; self-assembly

Hierarchically Structured Porous Materials: From Nanoscience to Catalysis, Separation, Optics, Energy, and Life Science - Su, B.-L.; Sanchez, C.; Yang, X.-Y. (Wiley-VCH Verlag GmbH & Co. KGaA, 2012)

(untitled) - Lu, A.-H.; Schüth, F. (Adv. Mater., 2006)

(untitled) - Lee, J.; Kim, J.; Hyeon, T. (Adv. Mater., 2006)

(untitled) - Nisticò, R.; Scalarone, D.; Magnacca, G. (Microporous Mesoporous Mater., 2017)

(untitled) - Liu, Q.; Tang, Z.; Ou, B.; Liu, L.; Zhou, Z.; Shen, S.; Duan, Y. (Mater. Chem. Phys., 2014)

(untitled) - Lazzari, M.; López-Quintela, M. A. (Adv. Mater., 2003)

(untitled) - Bagheri, S.; Hir, Z. A. M.; Yousefi, A. T.; Hamid, S. B. A. (Microporous Mesoporous Mater., 2015)

(untitled) - Biswas, A.; Bayer, I. S.; Biris, A. S.; Wang, T.; Dervishi, E.; Faupel, F. (Adv. Colloid Interface Sci., 2012)

(untitled) - Ozin, G. A.; Hou, K.; Lotsch, B. V.; Cademartiri, L.; Puzzo, D. P.; Scotognella, F.; Ghadimi, A.; Thomson, J. (Mater. Today, 2009)

(untitled) - Liu, T.; Burger, C.; Chu, B. (Prog. Polym. Sci., 2003)

(untitled) - Gates, B. D.; Qiaobing, X.; Stewart, M.; Ryan, D.; Willson, C. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Apolinário, A.; Quitério, P.; Sousa, C. T.; Proença, M. P.; Azevedo, J.; Susano, M.; Moraes, S.; Lopes, P.; Ventura, J.; Araújo, J. P. (J. Phys.: Conf. Ser., 2014)

(untitled) - Pierre, A. C.; Pajonk, G. M. (Chem. Rev., 2002)

(untitled) - Gallego, E. M.; Paris, C.; Díaz-Rey, M. R.; Martínez-Armero, M. E.; Martínez-Triguero, J.; Martínez, C.; Moliner, M.; Corma, A. (Chem. Sci., 2017)

(untitled) - Wan, Y.; Yang, H.; Zhao, D. Y. (Acc. Chem. Res., 2006)

(untitled) - Kumar, P.; Pournara, A.; Kim, K.-H.; Bansal, V.; Rapti, S.; Manos, M. J. (Prog. Mater. Sci., 2017)

(untitled) - Nisticò, R.; Tabasso, S.; Magnacca, G.; Jordan, T.; Shalom, M.; Fechler, N. (Langmuir, 2017)

(untitled) - Hentze, H.-P.; Antonietti, M. (Rev. Mol. Biotechnol., 2002)

(untitled) - Meseck, G. R.; Terpstra, A. S.; MacLachlan, M. J. (Curr. Opin. Colloid Interface Sci., 2017)

(untitled) - Nisticò, R.; Magnacca, G.; Antonietti, M.; Fechler, N. (Z. Anorg. Allg. Chem., 2014)

(untitled) - Boffa, V.; ten Elshof, J. E.; Blank, D. H. A. (Microporous Mesoporous Mater., 2007)

(untitled) - Nisticò, R.; Avetta, P.; Calza, P.; Fabbri, D.; Magnacca, G.; Scalarone, D. (Beilstein J. Nanotechnol., 2015)

(untitled) - Jin, J.; Wakayama, Y.; Peng, X.; Ichinose, I. (Nat. Mater., 2007)

(untitled) - Garcia Juez, R.; Boffa, V.; Blank, D. H. A.; ten Elshof, J. E. (J. Membr. Sci., 2008)

(untitled) - König, K.; Boffa, V.; Buchbjerg, B.; Farsi, A.; Christensen, M. L.; Magnacca, G.; Yue, Y. (J. Membr. Sci., 2014)

(untitled) - Brans, G.; Schroën, C. G. P. H.; van der Sman, R. G. M.; Boom, R. M. (J. Membr. Sci., 2004)

(untitled) - Schmuhl, R.; Sekulic, J.; Roy Chowdhury, S.; van Rijn, C. J. M.; Keizer, K.; van den Berg, A.; ten Elshof, J. E.; Blank, D. H. A. (Adv. Mater., 2004)

(untitled) - Ben, T.; Ren, H.; Ma, S.; Cao, D.; Lan, J.; Jing, X.; Wang, W.; Xu, J.; Deng, F.; Simmons, J. M.; Qiu, S.; Zhu, G. (Angew. Chem., Int. Ed., 2009)

(untitled) - El-Kaderi, H. M.; Hunt, J. R.; Mendoza-Cortés, J. L.; Côté, A. P.; Taylor, R. E.; O’Keeffe, M.; Yaghi, O. M. (Science, 2007)

(untitled) - Beiler, B.; Vincze, Á.; Svec, F.; Sáfrány, Á. (Polymer, 2007)

(untitled) - Rose, M.; Klein, N.; Senkovska, I.; Schrage, C.; Wollmann, P.; Böhlmann, W.; Böhringer, B.; Fichtner, S.; Kaskel, S. (J. Mater. Chem., 2011)

(untitled) - Olson, D. A.; Chen, L.; Hillmyer, M. A. (Chem. Mater., 2008)

(untitled) - Du, N.; Robertson, G. P.; Song, J.; Pinnau, I.; Thomas, S.; Guiver, M. D. (Macromolecules, 2008)

(untitled) - Kim, J. K.; Yang, S. Y.; Lee, Y.; Kim, Y. (Prog. Polym. Sci., 2010)

(untitled) - Riess, G. (Prog. Polym. Sci., 2003)

(untitled) - Darling, S. B. (Prog. Polym. Sci., 2007)

(untitled) - Albert, J. N. L.; Epps, T. H., III (Mater. Today, 2010)

(untitled) - Hou, S.; Zheng, J.; Zhang, S.; Li, S. (Polymer, 2015)

(untitled) - Matsen, M. W.; Bates, F. S. (Macromolecules, 1996)

(untitled) - Tseng, Y.-C.; Darling, S. B. (Polymer, 2010)

(untitled) - Cochran, E. W.; Garcia-Cervera, C. J.; Fredrickson, G. H. (Macromolecules, 2006)

(untitled) - Hu, H.; Gopinadhan, M.; Osuji, C. O. (Soft Matter, 2014)

(untitled) - Huang, C.-I.; Lodge, T. P. (Macromolecules, 1998)

(untitled) - Nandan, B.; Hsu, J.-Y.; Chen, H.-L. (Polym. Rev. (Philadelphia, PA, U. S.), 2006)

(untitled) - Tata, J.; Scalarone, D.; Lazzari, M.; Chiantore, O. (Eur. Polym. J., 2009)

(untitled) - Guo, F.; Andreasen, J. W.; Vigild, M. E.; Ndoni, S. (Macromolecules, 2007)

(untitled) - Okumura, A.; Nishikawa, Y.; Hashimoto, T. (Polymer, 2006)

(untitled) - Hashimoto, T.; Nishikawa, Y.; Tsutsumi, K. (Macromolecules, 2007)

(untitled) - Boudouris, B. W.; Frisbie, C. D.; Hillmyer, M. A. (Macromolecules, 2008)

(untitled) - Takahashi, A.; Rho, Y.; Higashihara, T.; Ahn, B.; Ree, M.; Ueda, M. (Macromolecules, 2010)

(untitled) - Crossland, E. J. W.; Kamperman, M.; Nedelcu, M.; Ducati, C.; Wiesner, U.; Smilgies, D.-M.; Toombes, G. E. S.; Hillmyer, M. A.; Ludwigs, S.; Steiner, U.; Snaith, H. J. (Nano Lett., 2009)

(untitled) - Crossland, E. J. W.; Ludwigs, S.; Hillmyer, M. A.; Steiner, U. (Soft Matter, 2007)

(untitled) - Zhou, N.; Bates, F. S.; Lodge, T. P. (Nano Lett., 2006)

(untitled) - Fu, G.-D.; Yuan, Z.; Kang, E.-T.; Neoh, K.-G.; Lai, D. M.; Huan, A. C. H. (Adv. Funct. Mater., 2005)

(untitled) - Jones, B. H.; Lodge, T. P. (Chem. Mater., 2010)

(untitled) - Uehara, H.; Kakiage, M.; Sekiya, M.; Sakuma, D.; Yamonobe, T.; Takano, N.; Barraud, A.; Meurville, E.; Ryser, P. (ACS Nano, 2009)

(untitled) - Uehara, H.; Yoshida, T.; Kakiage, M.; Yamanobe, T.; Komoto, T.; Nomura, K.; Nakajima, K.; Matsuda, M. (Macromolecules, 2006)

(untitled) - Chen, L.; Hillmyer, M. A. (Macromolecules, 2009)

(untitled) - Mao, H.; Hillmyer, M. A. (Macromolecules, 2005)

(untitled) - Zhang, M.; Yang, L.; Yurt, S.; Misner, M. J.; Chen, J.-T.; Coughlin, E. B.; Venkataraman, D.; Russell, T. P. (Adv. Mater., 2007)

(untitled) - Mao, H.; Hillmyer, M. A. (Soft Matter, 2006)

(untitled) - Glassner, M.; Blinco, J. P.; Barner-Kowollik, C. (Polym. Chem., 2011)

(untitled) - Fustin, C.-A.; Lohmeijer, B. G. G.; Duwez, A.-S.; Jonas, A. M.; Schubert, U. S.; Gohy, J.-F. (Adv. Mater., 2005)

(untitled) - Iannarelli, L.; Nisticò, R.; Avetta, P.; Lazzari, M.; Magnacca, G.; Calza, P.; Fabbri, D.; Scalarone, D. (Eur. Polym. J., 2015)

(untitled) - Phillip, W. A.; O’Neill, B.; Rodwogin, M.; Hillmyer, M. A.; Cussler, E. L. (ACS Appl. Mater. Interfaces, 2010)

(untitled) - Tseng, W.-H.; Chen, C.-K.; Chiang, Y.-W.; Ho, R.-M.; Akasaka, S.; Hasegawa, H. (J. Am. Chem. Soc., 2009)

(untitled) - Lo, K.-H.; Tseng, W.-H.; Ho, R.-M. (Macromolecules, 2007)

(untitled) - Olayo-Valles, R.; Guo, S.; Lund, M. S.; Leighton, C.; Hillmyer, M. A. (Macromolecules, 2005)

(untitled) - Grande, D.; Penelle, J.; Davidson, P.; Beurroies, I.; Denoyel, R. (Microporous Mesoporous Mater., 2011)

(untitled) - Chao, C.-C.; Wang, T.-C.; Ho, R.-M.; Georgopanos, P.; Avgeropoulos, A.; Thomas, E. L. (ACS Nano, 2010)

(untitled) - Yang, S. Y.; Park, J.; Yoon, J.; Ree, M.; Jang, S. K.; Kim, J. K. (Adv. Funct. Mater., 2008)

(untitled) - Melde, B. J.; Burkett, S. L.; Xu, T.; Goldbach, J. T.; Russell, T. P.; Hawker, C. J. (Chem. Mater., 2005)

(untitled) - Joo, W.; Park, M. S.; Kim, J. K. (Langmuir, 2006)

(untitled) - Hozumi, A.; Asakura, S.; Fuwa, A.; Shirahata, N. (J. Colloid Interface Sci., 2005)

(untitled) - Yang, S. Y.; Ryu, I.; Kim, H. Y.; Kim, J. K.; Jang, S. K.; Russell, T. P. (Adv. Mater., 2006)

(untitled) - Yang, S. Y.; Yang, J.-A.; Kim, E.-S.; Jeon, G.; Oh, E. J.; Choi, K. Y.; Hahn, S. K.; Kim, J. K. (ACS Nano, 2010)

(untitled) - Crossland, E. J. W.; Cunha, P.; Scroggins, S.; Moratti, S.; Yurchenko, O.; Steiner, U.; Hillmyer, M. A.; Ludwigs, S. (ACS Nano, 2010)

(untitled) - Drockenmuller, E.; Li, L. Y. T.; Ryu, D. Y.; Harth, E.; Russell, T. P.; Kim, H.-C.; Hawker, C. J. (J. Polym. Sci., Part A: Polym. Chem., 2005)

(untitled) - Leiston-Belanger, J. M.; Russell, T. P.; Drockenmuller, E.; Hawker, C. J. (Macromolecules, 2005)

(untitled) - Lodge, T. P.; Pudil, B.; Hanley, K. J. (Macromolecules, 2002)

(untitled) - Park, M. J.; Bang, J.; Harada, T.; Char, K.; Lodge, T. P. (Macromolecules, 2004)

(untitled) - Huang, Y.-Y.; Chen, H.-L.; Hashimoto, T. (Macromolecules, 2003)

(untitled) - Russell, T. P.; Karis, T. E.; Gallot, Y.; Mayes, A. M. (Nature, 1994)

(untitled) - Loo, Y.-L.; Register, R. A.; Ryan, A. J. (Macromolecules, 2002)

(untitled) - He, W.-N.; Xu, J.-T. (Prog. Polym. Sci., 2012)

(untitled) - Patterson, D.; Robard, A. (Macromolecules, 1978)

The Physics of Block Copolymers - Hamley, I. W. (Oxford University Press, 1998)

(untitled) - Burwell, R. L., Jr (Chem. Rev., 1954)

(untitled) - Kim, S. H.; Misner, M. J.; Russell, T. P. (Adv. Mater., 2008)

(untitled) - Kim, S. H.; Misner, M. J.; Xu, T.; Kimura, M.; Russell, T. P. (Adv. Mater., 2004)

(untitled) - Karunakaran, M.; Nunes, S. P.; Qiu, X.; Yu, H.; Peinemann, K.-V. (J. Membr. Sci., 2014)

(untitled) - Wang, Y.; Tong, L.; Steinhart, M. (ACS Nano, 2011)

(untitled) - Zhu, L.; Mimnaugh, B. R.; Ge, Q.; Quirk, R. P.; Cheng, S. Z. D.; Thomas, E. L.; Lotz, B.; Hsiao, B. S.; Yeh, F.; Liu, L. (Polymer, 2001)

(untitled) - Sidorenko, A.; Tokarev, I.; Minko, S.; Stamm, M. (J. Am. Chem. Soc., 2003)

(untitled) - Ciriminna, R.; Fidalgo, A.; Pandarus, V.; Béland, V.; Ilharco, L. M.; Pagliaro, M. (Chem. Rev., 2013)

Sol-gel Science: the Physics and Chemistry of Sol-gel Processing - Brinker, C. J.; Scherer, G. W. (Academic Press, 1990)

(untitled) - Schüth, F. (Angew. Chem., Int. Ed., 2003)

(untitled) - Lofgreen, J. E.; Ozin, G. A. (Chem. Soc. Rev., 2014)

(untitled) - Kreuzer, M.; Simão, C.; Diaz, A.; Sotomayor Torres, C. M. (Polymer, 2016)

(untitled) - Metwalli, E.; Körstgens, V.; Schlage, K.; Meier, R.; Kaune, G.; Buffet, A.; Couet, S.; Roth, S. V.; Röhlsberger, R.; Müller-Buschbaum, P. (Langmuir, 2013)

(untitled) - Chen, F.; Huang, L.; Li, Q. (Chem. Mater., 1997)

(untitled) - Yu, K.; Smarsly, B.; Brinker, C. J. (Adv. Funct. Mater., 2003)

(untitled) - Nisticò, R.; Scalarone, D.; Magnacca, G. (Microporous Mesoporous Mater., 2014)

(untitled) - Nisticò, R.; Magnacca, G.; Jadhav, S. A.; Scalarone, D. (Beilstein J. Nanotechnol., 2016)

(untitled) - Chandra, D.; Ohji, T.; Kato, K.; Kimura, T. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Scalarone, D.; Tata, J.; Caldera, F.; Lazzari, M.; Chiantore, O. (Mater. Chem. Phys., 2011)

(untitled) - Pevzner, S.; Regev, O.; Yerushalmi-Rozen, R. (Curr. Opin. Colloid Interface Sci., 1999)

(untitled) - Castel, C.; Favre, E. (J. Membr. Sci., 2018)

(untitled) - Goh, P. S.; Matsuura, T.; Ismail, A. F.; Hilai, N. (Desalination, 2016)

(untitled) - Lafleur, J. P.; Jönsson, A.; Senkbeil, S.; Kutter, J. P. (Biosens. Bioelectron., 2016)

(untitled) - Hamley, I. W. (Prog. Polym. Sci., 2009)

(untitled) - Samaddar, P.; Deep, A.; Kim, K.-H. (Chem. Eng. J., 2018)

(untitled) - Van Gough, D.; Juhl, A. T.; Braun, P. V. (Mater. Today, 2009)

(untitled) - Lee, J.; Orilall, M. C.; Warren, S. C.; Kamperman, M.; DiSalvo, F. J.; Wiesner, U. (Nat. Mater., 2008)

RSC Nanoscience and Nanotechnology N°11 - Lu, A.-H.; Zhao, D.; Wan, Y. (Nanocasting: a Versatile Strategy for Creating Nanostructured Porous Materials, 2010)

(untitled) - Nisticò, R. (Res. Chem. Intermed., 2017)

(untitled) - Sillanpää, M.; Chaker Ncibi, M.; Matilainen, A. (J. Environ. Manage., 2018)

(untitled) - Palma, D.; Bianco Prevot, A.; Celi, L.; Martin, M.; Fabbri, D.; Magnacca, G.; Chierotti, M. R.; Nisticò, R. (Catalysts, 2018)